Архітектурні підходи до розширення кінематики персонажа в середовищі Unreal Engine - Місько, Єгор Валерійович; Misko, Yehor (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті досліджено архітектурні обмеження базового класу UCharacterMovementComponent в Unreal Engine. Виявлені обмеження критичні для мережевих систем, де непередбачувані розриви кінематики ускладнюють алгоритми екстраполяції та компенсації затримки. Запропоновано підхід, заснований на перехопленні фізичних розрахунків під час колізії та використанні векторної алгебри замість непередбачуваної фізики твердих тіл. Розроблено математичну модель збереження імпульсу: використовуючи скалярний та векторний добутки нормалі поверхні, алгоритм обчислює дотичну траєкторію без втрати початкової швидкості. Сформульовано диференціальну модель контролю швидкості (Soft Cap), яка замінює базовий ліміт MaxWalkSpeed на алгоритм постійного асимптотичного зниження імпульсу. Інтеграція методу з проекцією вектора гравітації дозволила реалізувати фізично коректне накопичення інерції залежно від топології рівня. Практична імплементація довела перевагу Data-Driven підходу, забезпечивши збереження плавності кінематичних функцій та повну алгоритмічну керованість поведінки контролера. /// EN: The article examines the architectural limitations of the base class UCharacterMovementComponent in Unreal Engine, specifically concerning complex kinematic movements and momentum preservation. While highly optimized for standard bipedal locomotion, this component exhibits rigid constraints during high-velocity, physicsbased interactions. The identified limitations are critical for multiplayer networked systems, where unpredictable kinematic discontinuities and hard-coded collision responses severely complicate server-side extrapolation and client-side latency compensation algorithms, often leading to visual desynchronization in fast-paced scenarios. To address these fundamental issues, an innovative architectural approach is proposed based on intercepting lowlevel physical calculations during collision events. Instead of relying on the engine's default, often unpredictable rigid body dynamics for character collision resolution, the proposed architecture utilizes precise vector algebra. A robust mathematical model of momentum preservation has been developed and integrated into the custom movement logic. By using the scalar and vector products of the impacted surface normal, the algorithm calculates the optimal tangent trajectory. This allows the virtual character to glide along complex geometry without the abrupt loss of initial kinetic energy that typically occurs in the base engine implementation upon hitting an obstacle. Furthermore, a differential speed control model, defined as a “Soft Cap,” was formulated. This model systematically replaces the basic MaxWalkSpeed absolute limit, which traditionally truncates velocity vectors instantly and artificially. Instead, the Soft Cap employs an algorithm for the constant asymptotic reduction of momentum. This allows characters to temporarily exceed standard speed limits while smoothly decaying the excess velocity over time, drastically improving the fluidity of mechanics. Integrating this method with continuous gravity vector projection allowed for physically correct inertia accumulation strongly dependent on the level’s topology, dynamically translating gravitational pull into forward momentum on descents. Practical implementation proved the significant superiority of the Data-Driven approach. It ensures absolute smoothness of kinematic functions and full algorithmic controllability of the controller’s behavior, providing a highly scalable foundation for modern, movement-intensive mechanics.
Architectural approaches to extending character kinematics in the Unreal Engine environment
Keywords: Unreal Engine; архітектура програмних рушіїв; кінематика персонажа; векторна алгебра; збереження імпульсу; локомоція; розробка систем; game engine architecture; character kinematics; vector algebra; momentum preservation; locomotion; game development